Mechanism of cell death induced by the novel enzyme-prodrug combination, nitroreductase/CB1954, and identification of synergism with 5-fluorouracil - Palmer, D H (Nature Publishing Group, 2003)
Virus-directed enzyme prodrug therapy (VDEPT) utilising the bacterial enzyme nitroreductase delivered by a replication-defective adenovirus vector to activate the prodrug CB1954 is a promising strategy currently undergoing clinical trials in patients with a range of cancers. An understanding of the mechanism of tumour cell death induced by activated CB1954 will facilitate this clinical development. Here, we report that activated CB1954 kills cells predominantly by caspase-dependent apoptosis. This may have important implications for the generation of immune-mediated bystander effects. Further, the use of a replication-defective adenovirus vector to deliver nitroreductase may negatively affect cellular apoptotic pathways stimulated by activated CB1954. Finally, examination of nitroreductase/CB1954 in combination with conventional chemotherapy reveals a synergistic interaction with 5-fluorouracil. These data will facilitate the further development and future clinical trial design of this novel therapy.